Development of a Visible Reverse Transcription-Loop-Mediated Isothermal Amplification Assay for the Detection of Rift Valley Fever Virus - Han, Qiuxue; Zhang, Shengnan; Liu, Dongping; Yan, Feihu; Wang, Hualei; Huang, Pei; Bi, Jinhao; Jin, Hongli; Feng, Na; Cao, Zengguo; Gao, Yuwei; Chi, Hang; et al. (Frontiers in Microbiology, 2020)
Rift Valley fever (RVF) is a severe infectious disease, which can through mosquito bites, direct contact and aerosol transmission infect sheep, goats, people, camels, cattle, buffaloes, and so on. In this paper, a conserved region of the S RNA segment of Rift Valley fever virus (RVFV) ZH501 strain was used as target sequence. The RVFV RT-LAMP-VF assay was successfully established combined reverse transcription-loop-mediated isothermal amplification with a vertical flow visualization strip. The detection limit is up to 1.94 × 100 copies/μl of synthesized RVFV-RNA. RNA extracted from cell culture of an inactivated RVFV-BJ01 strain was also used as templates, and the detection limit is 1.83 × 103 copies/μl. In addition, there was no cross-reactivity with other viruses that can cause similar fever symptoms. The RVFV-LAMP-VF assay exhibited very high levels of diagnostic sensitivity, which had 100-fold more sensitive than RVFV real-time RT-PCR assay. Accordingly, the RVFV RT-LAMP-VF assay developed in this study is suitable for the rapid and sensitive diagnosis of RVFV without specialized equipment and can rapidly complete detection within 60 min, and the results are visible by vertical flow visualization strip within 5 min.